Religious Happiness and Spiritual Formation for Learning to Live Together in Indonesia's Plural Society - GP Harianto (RaSAIL Media Group, Semarang, Indonesia, 2026)
This article examines how religious happiness and spiritual formation can serve as conceptual foundations for learning to live together in Indonesia's plural society. The unit of analysis consists of academic literature on religiosity, happiness, spiritual formation, pluralism, and social coexistence, with particular attention to studies relevant to the Indonesian context. The article aims to clarify the relationship between personal religious well-being and the social ethics of living together in a religiously diverse society. Drawing on a qualitative literature review, this study analyzes recent scholarly work to identify key conceptual patterns linking spirituality, happiness, and interreligious coexistence. The findings show that religious happiness is not limited to inward spiritual satisfaction but is also shaped by moral formation, spiritual practice, lived religious values, and service-oriented engagement with others. The novelty of this article lies in its integrative framework that connects personal spiritual formation with the civic and ethical task of sustaining social harmony in plural Indonesia. By locating religious happiness within the constitutional and Pancasila-based vision of coexistence, this study contributes a conceptual basis for developing more inclusive models of religious education, spiritual formation, and civic learning that support religious moderation, mutual respect, and social integration in contemporary Indonesia.